Corticosteroid-Refractory Myositis After Dual BRAF and MEK Inhibition in a Patient with BRAF V600E-Mutant Metastatic Intrahepatic Cholangiocarcinoma - Timothy P. DiPeri; Mehmet Demirhan; Daniel D. Karp; Siqing Fu; David S. Hong; Vivek Subbiah; Joann Lim; Leomar Y. Ballester; Jean H. Tayar; Maria E. Suarez-Almazor; Milind Javle; Funda Meric-Bernstam (Journal of Immunotherapy and Precision Oncology, 2022)
Intrahepatic cholangiocarcinoma is a rare malignancy, which is rich in actionable alterations. Genomic aberrations in the mitogen-activated protein kinase (MAPK) pathway are common, and BRAF exon 15 p.V600E mutations are present in 5–7% of biliary tract cancers (BTC). Dual inhibition of BRAF and MEK has been established for BRAF-mutated melanoma and lung cancer, and recent basket trials have shown efficacy of this combination in BRAF V600E-mutant BTCs. Here, we report on a patient with BRAF exon 15 p.V600E mutant metastatic intrahepatic cholangiocarcinoma who was started on BRAF and MEK inhibition with vemurafenib and combimetinib. Shortly thereafter, he developed debilitating myositis, which was refractory to corticosteroids, requiring therapeutic plasma exchange and intravenous immunoglobulin. We also review BRAF as a target in BTCs, relevant clinical trials, and adverse events associated with BRAF and MEK inhibition.